Craniofacial tendon development—Characterization of extracellular matrix morphology and spatiotemporal protein distribution - Korntner, Stefanie H.; Jana, Aniket; Kinnard, Elizabeth; Leo, Emily; Beane, Timothy; Li, Xianmu; Sengupta, Rohit; Becker, Lauren; Kuo, Catherine K. (Frontiers in Cell and Developmental Biology, 2022)
Craniofacial (CF) tendons are often affected by traumatic injuries and painful disorders that can severely compromise critical jaw functions, such as mastication and talking. Unfortunately, tendons lack the ability to regenerate, and there are no solutions to restore their native properties or function. An understanding of jaw tendon development could inform tendon regeneration strategies to restore jaw function, however CF tendon development has been relatively unexplored. Using the chick embryo, we identified the jaw-closing Tendon of the musculus Adductor Mandibulae Externus (TmAM) and the jaw-opening Tendon of the musculus Depressor Mandibulae (TmDM) that have similar functions to the masticatory tendons in humans. Using histological and immunohistochemical (IHC) analyses, we characterized the TmAM and TmDM on the basis of cell and extracellular matrix (ECM) morphology and spatiotemporal protein distribution from early to late embryonic development. The TmAM and TmDM were detectable as early as embryonic day (d) 9 based on histological staining and tenascin-C (TNC) protein distribution. Collagen content increased and became more organized, cell density decreased, and cell nuclei elongated over time during development in both the TmAM and TmDM. The TmAM and TmDM exhibited similar spatiotemporal patterns for collagen type III (COL3), but differential spatiotemporal patterns for TNC, lysyl oxidase (LOX), and matrix metalloproteinases (MMPs). Our results demonstrate markers that play a role in limb tendon formation are also present in jaw tendons during embryonic development, implicate COL3, TNC, LOX, MMP2, and MMP9 in jaw tendon development, and suggest TmAM and TmDM possess different developmental programs. Taken together, our study suggests the chick embryo may be used as a model with which to study CF tendon extracellular matrix development, the results of which could ultimately inform therapeutic approaches for CF tendon injuries and disorders.